KAJIAN SUBSTITUSI TEPUNG TAPIOKA DAN PENAMBAHAN GLISEROL MONOSTEARAT PADA PEMBUATAN ROTI TAWAR - Basuki, Enny Karti; Yulistyani, Ratna; Hidayat, Roni (REKAPANGAN, 2011)
Bread  is  one  of  fermentation  product  and  consumer  likely  made  form  wheat  flour  , bread  have  difference  taste  and  softness.  Using  cassava  flour    to  product    bread that can increased  various  bread  product  and  value.  The  purpose  of  this  research  is to  find    the  best combination between substitution cassava flour and glycerol monostearat addition for quality of bread.  Experimental  design  employed  in  this  research  is  randomized  completely  design consisting  of  two  factors  and  three  replications,   the  first  factors  substitution  cassava  flour (10%, 20%, and 30%) and the second factor is glycerol monostearat  addition (1%,2%,3%,4% and 5%). The best treatment was combination of cassava flour 10%  and glycerol monostearat addition 4%. This bread product has taste score 229,5, color score 195 and texture score 236, water content 29,34 %, protein 7,127%, fat 2,793%, starch 47,657%, loaf volume 347%, texture 0,915 mm/gr. det  and porous size 1,214 mm2.Keyword : bread, cassava starch flour, glycerol monostearat.